2017
DOI: 10.18203/2320-6012.ijrms20173555
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of FESS and septoplasty with FESS in cases of DNS with chronic maxillary sinusitis

Abstract: Background: Present study compares basic FESS and septoplasty with FESS alone in DNS with maxillary sinusitis.Methods: Sixty patients of DNS with chronic maxillary sinusitis were divided into two groups alternatively. After pre-operative symptoms score and computerized tomography (CT scan), twenty patients underwent FESS with septoplasty (group A) and other 20 underwent FESS alone (group B) under local anaesthesia and topical 4% lignocaine with 1:1000 adrenaline. At 6 weeks, post-operative symptom score and CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
(19 reference statements)
0
7
0
2
Order By: Relevance
“…The study done by Thakur et al 2017 showed that the success rate was higher in patients with septoplasty alone as compared to those in FESS with septoplasty suggesting adequacy of septoplasty alone in management of chronic maxillary sinusitis with DNS [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study done by Thakur et al 2017 showed that the success rate was higher in patients with septoplasty alone as compared to those in FESS with septoplasty suggesting adequacy of septoplasty alone in management of chronic maxillary sinusitis with DNS [2].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic rhinosinusitis is one of the most common diseases in many parts of the world. CRS is a clinical diagnosis and imaging is only indicated after adequate medical treatment; therefore, imaging should be interpreted considering history, examination, and response to medical treatment [2]. Nasal septum deviation can disturb nasal physiology, and it can be combined with conchal hypertrophy or other anatomical variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2005, Bayiz U et al concluded that septoplasty alone can be adequate treatment of chronic rhinosinusitis with septal deviation. 5 However, with the extensive use of endoscope in ENT surgeries, septoplasty combined with FESS has shown better symptom relief 6 . Hence the logical ease of combining FESS with endoscopic septoplasty.…”
Section: Conventional Septoplastymentioning
confidence: 99%